Nurses' Behavior Towards the Implementation of the International Patient Safety Goals: A Scoping Review - Indriyani Indriyani; Zahroh Shaluhiyah; Daru Lestantyo (GLOBAL HEALTH SCIENCE GROUP, 2026)
This study is to shed light on how nurses in hospitals apply the International Patient Safety Goals (IPSGs) and examine how they might be applied as evidence based procedures to assist hospitals in raising patient safety dan quality of care. This review aims to clarify the implementation of IPSGs by nurses and analyze them as evidence based practices to improve safety and high quality hospital care. This study used a scoping review method, articles collected from Google Scholar and GARUDA portal database. Articles reviewed were published between 2020 and 2025. Out of 126 articles screened, 13 eligible articles were included for review. Findings revealed that the implementation of IPSGs by nurses to prevent patient safety incidents in hospitals includes: nurses’ knowledge of patient safety procedures, nurses’ attitudes in implementing patient safety, facilities and infrastructure supporting patient safety goals, regulations related to patient safety, peer support, and leadership support in patient safety practices. Nurses as the dominant healthcare professionals who are in direct contact with patients, hold a crucial role in implementing patient safety.